Necesidad de reformar el código de la niñez y adolescencia en relación a incorporar medidas alternativas a la privación de la libertad por apremio personal del alimentante, para garantizar el cumplimiento de la obligación alimenticia - Delgado Montoya, Carlos Antonio (2014)
The present research is titled : "NEED FOR REFORM CODE OF CHILDREN AND ADOLESCENTS IN MAINSTREAM ALTERNATIVE MEASURES REGARDING THE DEPRIVATION OF LIBERTY OBLIGOR UNDER COERCION STAFF TO ENSURE COMPLIANCE WITH THE DUTY FOOD" and is object studying a legal problem of social and human involvement proceed to describe below. Pursuant to Article 22 of Title V, Book II of the Code of Children and Adolescents, where the principal to the provision of food, ie the parent fail to pay two or more child support, Judge of the Family, Women, Children and Adolescents, at the request of the actor may order the respondent's personal urgency for up to thirty days, and in case of recidivism will be extended for sixty days, up to a maximum of one hundred eighty days. As stated above, the urge staff, is a protective measure personal, involving the imprisonment of obliged to provide food, through which it seeks to compel compliance with the obligation owed, and ensure the right of children and adolescents, to receive the necessary assistance for their survival and proper development. However, this purpose is not met effectively, that deprivation of freedom prevents the obligor may have access to forms of production, so it is very difficult to meet the obligation. Thus generating a problem that causes the child or adolescent does not receive the benefit that it requires. 5 As noted, it would be the Code of Children and Adolescents, consider that the Judge or Justice of the Family, Women, Children and Adolescents, who knows the process, alternative security measures can be applied to urge staff who involve forced participation in productive activities aimed at obtaining the resources needed to meet alimony, thus satisfying food needs, while ensuring that it meets the best interests of children and adolescents. The study is developed in accordance with the rules in force in the Academic System Regulations of the National University of Loja, and is supported by theoretical, and field results, which confirm the existence of the problem and support the approach of the corresponding amendment to the Code of Children and Adolescents, held at the end of work.